Relation between planimetric and volumetric measurements of permafrost coast erosion: a case study from Herschel Island, western Canadian Arctic - Obu, Jaroslav; Lantuit, Hugues (Prof. Dr.); Fritz, Michael (Dr.); Pollard, Wayne H.; Sachs, Torsten; Guenther, Frank (Polar Research, 2016)
Ice-rich permafrost coasts often undergo rapid erosion, which results in land loss and release of considerable amounts of sediment, organic carbon and nutrients, impacting the near-shore ecosystems. Because of the lack of volumetric erosion data, Arctic coastal erosion studies typically report on planimetric erosion. Our aim is to explore the relationship between planimetric and volumetric coastal erosion measurements and to update the coastal erosion rates on Herschel Island in the Canadian Arctic. We used high-resolution digital elevation models to compute sediment release and compare volumetric data to planimetric estimations of coastline movements digitized from satellite imagery. Our results show that volumetric erosion is locally less variable and likely corresponds better with environmental forcing than planimetric erosion. Average sediment release volumes are in the same range as sediment release volumes calculated from coastline movements combined with cliff height. However, the differences between these estimates are significant for small coastal sections. We attribute the differences between planimetric and volumetric coastal erosion measurements to mass wasting, which is abundant along the coasts of Herschel Island. The average recorded coastline retreat on Herschel Island was 0.68m a(-1) for the period 2000-2011. Erosion rates increased by more than 50% in comparison with the period 1970-2000, which is in accordance with a recently observed increase along the Alaskan Beaufort Sea. The estimated annual sediment release was 28.2 m(3) m(-1) with resulting fluxes of 590 kg C m(-1) and 104 kg N m(-1).